BRIDGING STUDENTS' SPEAKING SKILL THROUGH SPINNING WHEEL MEDIA AT SMP NEGERI 1 BONTOMARANNU - Ira Maya; Nurdevi Bte Abdul; Awalia Azis (FKIP Unismuh Makassar, 2022)
This research aimed to verify whether the use of Spinning Wheel Media effective to bridging students’ speaking skill in term of pronunciation and vocabulary after being taught through Spinning Wheel Media at the first grade of SMP Negeri 1 Bontomarannu. The researcher applied pre-experimental method with one group pre-test post-test design and the data were collected by giving pre-test, treatment and post-test. The sample of the research was VII 3 of SMP Negeri 1 Bontomarannu which consisted of 16 students. The population of this study was the first grade students of SMP Negeri 1 Bontomarannu which consisted of 296 students in the academic year of 2021/2022. The sample was taken by cluster random sampling technique to select the sample of the research. The technique used for obtaining data was speaking test. The research findings show that the mean score of the students in pronunciation is proved by post-test 53.12 is higher than the mean score of the students in pre-test 34.37. Mean score of the students vocabulary is proved by pre-test 42.18 and post-test 75 and the hypothesis t-test value were 6.54. It means that Ha is accepted. Based on the findings that there is significance difference between the result of pre-test and post-test. Spinning Wheel Media is very good in enhance the students speaking skill in terms of pronunciation and vocabulary.